Assessment of Bioenergy Cropping Scenarios for the Boone River Watershed in North Central Iowa, United States1. (24th October 2017) - Gassman, Philip W.; Valcu‐Lisman, Adriana M.; Kling, Catherine L.; Mickelson, Steven K.; Panagopoulos, Yiannis; Cibin, Raj; Chaubey, Indrajeet; Wolter, Calvin F.; Schilling, Keith E.
Abstract: Several biofuel cropping scenarios were evaluated with an improved version of Soil and Water Assessment Tool (SWAT) as part of the CenUSA Bioenergy consortium for the Boone River Watershed (BRW), which drains about 2, 370 km 2 in north central Iowa. The adoption of corn stover removal, switchgrass, and/or Miscanthus biofuel cropping systems was simulated to assess the impact of cellulosic biofuel production on pollutant losses. The stover removal results indicate removal of 20 or 50% of corn stover in the BRW would have negligible effects on streamflow and relatively minor or negligible effects on sediment and nutrient losses, even on higher sloped cropland. Complete cropland conversion into switchgrass or Miscanthus, resulted in reductions of streamflow, sediment, nitrate, and other pollutants ranging between 23‐99%. The predicted nitrate reductions due to Miscanthus adoption were over two times greater compared to switchgrass, with the largest impacts occurring for tile‐drained cropland. Targeting of switchgrass or Miscanthus on cropland ≥2% slope or ≥7% slope revealed a disproportionate amount of sediment and sediment‐bound nutrient reductions could be obtained by protecting these relatively small areas of higher sloped cropland. Overall, the results indicate that all biofuel cropping systems could be effectively implemented in the BRW, with the most robust approach being corn stover removal adopted on tile‐drained cropland in combination with a perennial biofuel crop on higher sloped landscapes. Editor's note : This paper is part of the featured series on SWAT Applications for Emerging Hydrologic and Water Quality Challenges. See the February 2017 issue for the introduction and background to the series .